Evaluating the Summer Thermal Structure of Southern Green Bay, Lake Michigan - (:unkn) unknown (My University, 2013)
The summer thermal structure of southern Green Bay, Lake Michigan was evaluated using cable moorings equipped with thermistors and a near real-time coastal monitoring buoy. The net heat flux for the southern bay was calculated over the study period. Cold water intrusions from Lake Michigan were tracked using water temperature, with the path of these water masses tracking along the western shore of Green Bay. Water clarity was measured across the study region as kd. Surface diel warming was evaluated and compared with meteorological forcing variables and sensible and latent heat flux to determine the effect of water clarity on the overall thermal structure of Green Bay for the study period. Interannual climate and variation in observed thermal structure at a station in the bay is considered between 2011 and 2012.
Keywords: Green Bay; Heat Budget; Heat Flux; Light Extinction Coefficient; Monitoring Buoy; Water Clarity